Quality assurance of biomedical equipment repair process on technical condition - Кучеренко, Валентина Леонідівна (Technology audit and production reserves, 2014)
Construction of a system of biomedical equipment repair on the actual technical condition is considered, and results of research in this area are given in the paper. The purpose of the research is to analyze the ways of quality assurance of biomedical equipment repair process in transition to the operation on the actual technical condition. Using the methods and means for the repair process stages automation allows to estimate actual technical condition of biomedical equipment. The analysis of the existing repair system for determining the factors, affecting the repair process quality and operating efficiency in general was conducted in the paper. The developed biomedical equipment repair system structure, which is based on the introduction of production and information technologies, allows to repair on the actual technical condition that is determining in ensuring the process quality. The research results can be applied by maintenance engineering staff, who work in biomedical institutions, as well as specialists of production and service centers of the biomedical-technical industry.